High‐Performance Semitransparent Tandem Solar Cell of 8.02% Conversion Efficiency with Solution‐Processed Graphene Mesh and Laminated Ag Nanowire Top Electrodes. Issue 12 (2nd May 2014) - Yusoff, Abd. Rashid bin Mohd; Lee, Seung Joo; Shneider, Fabio Kurt; da Silva, Wilson Jose; Jang, Jin
<x xml:space="preserve">Abstract</x> A high‐performance semitransparent tandem solar cell that uses solution‐processed graphene mesh and laminated Ag NW as a transparent anode and cathode, respectively, is demonstrated. The laminated top electrode can be deposited without causing any damage to the underneath organic solar cells. Power conversion efficiencies of 8.02% and 6.47% are obtained when the light is projected from the solution‐processed graphene mesh and laminated AgNW, respectively. The performance of the tandem cell is found to be comparable to a tandem solar cell fabricated using commercially available indium tin oxide. These findings offer a high‐performance device and open a new pathway in searching for a potential replacement to the frequently used transparent conducting electrodes.